Bossypants - Fey, Tina, 1970- (New York : Little, Brown, 2011)
The breakout star of "Saturday Night Live" and "30 Rock" gives a humorous account of her life, as well as behind- the-scenes stories from her hit shows.
"A Reagan Arthur book."
Keywords: Fey, Tina, -- 1970-; Women comedians -- United States -- Biography; Women television personalities -- United States -- Biography; American wit and humor